PENGARUH KONSUMSI AIR MINUM REVERSE OSMOSIS (RO) TERHADAP LAJU ALIRAN, pH, DAN VISKOSITAS SALIVA PADA SISWA SMA NEGERI 10 FAJAR HARAPAN BANDA ACEH - Santi Chismirina; Ridha Andayani; Afrina .; Putri Humaira Nanda Ibrahim; Hafizh Gunawan Amri (Journal of Syiah Kuala Dentistry Society, 2019)
One drink that is processed by the reverse osmosis method is Reverse Osmosis (RO) drinking water.Through this method, all micro particles contained in filtered water including essential minerals. Thereduction in essential minerals can reduce the activation function of salivary gland secretory cellsand it will have an impact on salivary flow, pH, and viscosity. This study aims to determine the effectof RO drinking water consumption to the flow rate, pH, and viscosity of saliva on students of FajarHarapan Senior High School Banda Aceh. The study subjects consisted of 45 subjects who consumedRO drinking water as the treatment group and 8 subjects who did not consume RO drinking water asa control group. Saliva from the treatment and control group subjects was collected by spittingmethod to measure the flow rate, pH, and viscosity of saliva. The results of the study that wereanalyzed using the unpaired T test showed that there was no effect of RO drinking water consumptionon the flow rate, pH, and viscosity of saliva in SMA Negeri 10 Fajar Harapan Banda Aceh. Based onthe results of the research, it can be concluded that the consumption of RO drinking water does notaffect the flow rate, pH and viscosity of the saliva in students of Fajar Harapan Senior High SchoolBanda Aceh. Keywords : Essential minerals, Calcium, Magnesium, Spitting method, pH meter.